Synthesis and antibacterial activity of novel 4″-O-(1-aralkyl-1, 2, 3-triazol-4-methyl-carbamoyl) azithromycin analogs. Issue 16 (15th August 2017) - Wang, Yinhu; Cong, Chao; Chai, Wern Chern; Dong, Ruiqian; Jia, Li; Song, Di; Zhou, Ziteng; Ma, Shutao
Graphical abstract: The novel 4″- O -(1-aralkyl-1, 2, 3-triazol-4-methyl-carbamoyl) azithromycin analogs exhibited excellent in vitro antibacterial activity against various susceptible and resistant pathogens. Highlights: 1, 2, 3-Triazol analogs of azithromycin were designed and synthesized. These analogs were evaluated for their in vitro antibacterial activity. They exhibited excellent activity against susceptible and -resistant strains. Compounds9g, 9h, 9j and9k exerted potent and broad spectrum antibacterial activity. Abstract: Three novel structural series of 4″- O -(1-aralkyl-1, 2, 3-triazol-4-methyl-carbamoyl) azithromycin analogs were designed, synthesized and evaluated for their in vitro antibacterial activity. All the target compounds exhibited excellent activity against erythromycin-susceptible Streptococcus pyogenes, and significantly improved activity against three phenotypes of erythromycin-resistant Streptococcus pneumoniae compared with clarithromycin and azithromycin. Among the three series of azithromycin analogs, the novel series of 11, 4″-disubstituted azithromycin analogs9a –k exhibited the most effective and balanced activity against susceptible and resistant bacteria. Among them, compound9j showed the most potent activity against Staphylococcus aureus ATCC25923 (0.008 µg/mL) and Streptococcus pyogenes R2 (1 µg/mL). Besides, all the 11, 4″-disubstituted azithromycin analogs9a –k except9f shared the identical activity with the MIC value <0.002 µg/mL against Streptococcus pyogenes S2. Furthermore, compounds9g, 9h, 9j and9k displayed significantly improved activity compared with the references against all the three phenotypes of resistant S. pneumoniae . Particularly, compound9k was the most effective (0.06, 0.03 and 0.125 µg/mL) against all the erythromycin-resistant S. pneumoniae expressing the erm gene, the mef gene and the erm and mef genes, exhibiting 2133, 133 and 2048-fold more potent activity than azithromycin, respectively.